Perbandingan efek perendaman resin komposit nanohybrid dalam larutan kopi luwak dengan larutan teh terhadap terjadinya diskolorasi - Clarita Utami; Member Reni Purba; Cindy Denhara Wijaya; Suci Erawati (Prima Journal of Oral and Dental Sciences, 2019)
Recently, most commonly used tooth filling was composite resin. The newest type of composite resin recently used was nanohybrid composite resin that has more strength and better color stability. Although it has good color stability, there was still had possibility discoloritation happened. The focus of this study was to find out the difference of discoloration between nanohybrid composite resin which were submerged in two different solutions which were civet coffee solution and tea solution. This research used 32 nanohybrid composite resin which were divided in two groups, and submerged  for 7 days. The discoloration of nanohybrid composite resin was measured before and after submersion using chromameter. The results of the statistical analysis of the independent t-test showed no significant difference in change mean color with  p=0.425 (p> 0.05) in submersion nanohybrid composite resin in both solutions. The conclusion of this study is that the color change of nanohybrid composite resin between two groups is not significantly different